An analysis of stromal expression of CD10 in invasive ductal carcinoma of breast and its correlation with histological grade - G. S., Thiriveni Balajji; S., Ulaganathan; Venkatachalam, A. Suresh; Akila, K. B.; Lavanya, K. B.; Vijayalakshmi, S. (International Journal of Research in Medical Sciences, 2017)
Background: Breast cancer is one of the most common cancers among women in India. Stroma has an important role in the pathogenesis of carcinoma of breast. Stromal marker can be novel marker for assessing the prognosis of breast cancer. Methods: With the representative sections of 30 invasive ductal carcinoma of breast NOS type Hematoxylin and eosin staining was done. Immunohistochemistry was done with CD10. CD10 expression in stroma in cases and control slides were studied and statistically analyzed with histopathological grade. Results: 46% (14 out of 30) of cases showed strong positivity for stromal CD10. Only two cases of strong positivity for CD10 were noted in the adjacent normal breast parenchyma. Stromal expression of CD10 had a statistically significant association with breast carcinoma than in control slides, p value is 0.002. 77% (10 out of 13) of CD10 positive cases were high grade carcinomas. Association of CD10 expression with high grade tumour was statistically significant (p value is 0.04 which is less than 0.05). No association was found with mean age. Conclusions: As the grade of breast carcinoma increases the stromal expression of CD10 is increased. Stromal CD10 expression is directly correlated with higher tumour grade. CD10 could be used as novel prognostic marker and used to develop newer drugs.